A randomised prospective comparison of the Flamingo Wallstent and Ultraflex stent for palliation of dysphagia associated with lower third oesophageal carcinoma. (1st July 2003) - Sabharwal, T; Hamady, M S; Chui, S; Atkinson, S; Mason, R; Adam, A
Abstract : Background: Covered metallic oesophageal stents offer effective palliation of malignant oesophageal strictures. However, first generation devices were associated with a high rate of migration, particularly when used in the lower oesophagus. Aim: To compare the rate of complications and palliative effect of two newer covered metallic oesophageal stents. Patients and methods: We performed a prospective randomised study using two of these newer stent designs in the treatment of malignant lower third oesophageal tumours. Fifty three patients with dysphagia due to inoperable oesophageal carcinoma involving the lower third of the oesophagus were randomly selected to receive either a Flamingo covered Wallstent (Boston Scientific Inc., Watertown, Massachusetts, USA) or an Ultraflex covered stent (Boston Scientific Inc.). Dysphagia was scored on a five point scale, recorded before stent insertion, the day after, and at least one month later at follow up. Technical success, early and late complications (perforation, migration, severe gastro-oesophageal reflux, haematemesis, and reobstruction due to tumour overgrowth) were also recorded. Results: In both stent groups, a significant improvement in dysphagia score was seen both the next day post stenting and at late follow up (p<0.05). No significant difference was seen in the improvement in dysphagia between the two groups (p>0.1). The frequency of complications encountered in the two groups was similar. Three patients in the Ultraflex group required two stents at primary stenting. Conclusion: The two types of stent are equally effective in the palliation of dysphagia associated with lower third oesophageal malignancy and the complication rates associated with their use are comparable.